Self‐adaptive proactive routing scheme for mobile ad‐hoc networks. Issue 2 (1st March 2015) - Son, Tran The; Le Minh, Hoa; Sexton, Graham; Aslam, Nauman
Abstract : This study introduces a routing model which has the ability to detect the mobile ad‐hoc network (MANET) mobility states and self‐adapt routing metrics accordingly. In this model, nodes rely on theirs mobility indicator to detect whether the network is relatively static or mobile and hence switch the routing metric to either expected transmission count (ETX) or mobility factor (MF), respectively. The proposed model takes advantages of both ETX and MF metrics thus enhancing the overall routing performance for MANET in different mobility states. Packet delivery ratio increases 10% in both static and mobile conditions whereas the number of drop packets reduces half compared with the original optimised link state routing protocol.